Associations of Dietary Copper, Selenium, and Manganese Intake With Depression: A Meta-Analysis of Observational Studies - Ding, Jun; Zhang, Yi (Frontiers in Nutrition, 2022)
Abstract Objective: To comprehensively summarize the evidence on the associations of dietary copper, selenium and manganese intake with depression based on a meta-analysis of observational studies. Methods: The electronic database of PubMed, Web of Science and Embase were searched up to January 7, 2022, for observational studies on the associations of dietary copper, selenium and manganese intake with depression (no restriction was set for the initiate time). The pooled relative risk (RR) of depression for the highest versus lowest dietary copper, selenium and manganese intake category were calculated. Results: A total of 11 observational studies (61430 participants) were identified as meeting the inclusion criteria. Specifically, 5 studies were related to the dietary copper intake. The overall multi-variable adjusted RR demonstrated that dietary copper intake was inversely associated with depression (RR=0.63, 95%CI: 0.52 to 0.76; P<0.001; I2=2.4%). With regard to the dietary selenium intake, 6 studies were identified for meta-analysis. The overall multi-variable adjusted RR showed that dietary selenium intake was also negatively associated with depression (RR=0.63, 95%CI: 0.54 to 0.74; P<0.001; I2=37.8%). In addition, 4 studies were specified for the dietary manganese intake, and the overall multi-variable adjusted RR indicated a negative relationship between dietary manganese intake and depression (RR=0.71, 95%CI: 0.58 to 0.86; P<0.001; I2=0.0%). Conclusions: Our results suggest a negative relationship between dietary copper, selenium and manganese intake and depression, respectively. However, due to the limited prospective evidence, our results are restricted to cross-sectional design that precludes causal relationships. More well-designed prospective cohort studies are still needed.